2021
DOI: 10.1088/1742-6596/2076/1/012050
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of manganese dioxide doped with metal for the treatment of phenolic wastewater

Abstract: The wastewater containing phenol is harmful, and the process is complicated, photocatalytic oxidation technology is believed to be the greenest and promising strategy for contaminants removal because of the solar energy utilization and no additional oxidants. Herein, manganese dioxide(MnO2) doped with metal was fabricated by a low-temperature hydrothermal method, the specific surface area of MnO2 photocatalyst was significantly enhanced by doping metal ion. This making the photocatalytic performance improved o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…[ 40 ] In another literature, Qin et al prepared metal‐doped MnO 2 by a low‐temperature hydrothermal method to evaluate the photodegradation activity of MnO 2 on the phenol, and the results showed that the photocatalytic efficiency of pure MnO 2 toward phenol could reach 52%. [ 41 ] Apparently, MnO 2 ‐based materials have made remarkable achievements in photothermal evaporation and have also been proven in photocatalytic degradation of various organic contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…[ 40 ] In another literature, Qin et al prepared metal‐doped MnO 2 by a low‐temperature hydrothermal method to evaluate the photodegradation activity of MnO 2 on the phenol, and the results showed that the photocatalytic efficiency of pure MnO 2 toward phenol could reach 52%. [ 41 ] Apparently, MnO 2 ‐based materials have made remarkable achievements in photothermal evaporation and have also been proven in photocatalytic degradation of various organic contaminants.…”
Section: Introductionmentioning
confidence: 99%